The Boarders in the Emergency Department (BED) study. Issue 5 (23rd April 2008) - Gilligan, P; Winder, S; Singh, I; Gupta, V; Kelly, P O; Hegarty, D
Abstract : Background and objectives: In the Boarders in the Emergency Department (BED) study the impact of overcrowding due to boarders on patients' mortality and the likelihood of being diagnosed with methicillin resistant Staphylococcus aureus (MRSA) during admission was examined. With regard to efficiency, the impact of overcrowding on the time to first medical assessment for admitted patients, the number of patients leaving without being seen, and the rate of admission as a percentage of total emergency department attendances was explored. Methods: The retrospective cohort analysis study of all emergency department admissions was performed using information accessed via the Diver Solution. The software integrated information from several databases. Results: The average number of patients awaiting hospital admission in the emergency department at 09:00 was 20.4 (range 0–45). The average duration of stay in the emergency department following the decision to admit was 16.1 h (range 0–161 h). The number who did not wait (DNW) to be seen was strongly correlated with the time waiting for medical assessment, which in turn was correlated with the total number of attendances to the emergency department (p<0.001). The elderly waited longer for admission and had the highest mortality and the highest chance of being diagnosed with MRSA during their overall admission. Conclusion: It is wrong for patients who are sick enough to require admission to hospital to be kept in the emergency department, and the entire health system must respond to their plight.